Peer Review - HE EFFECT OF BEHAVIOUR FACTOR ON THE SEISMIC PERFORMANCE OF LOW-RISE AND HIGH-RISE RC BUILDINGS - Ade Faisal (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study investigates the performance of RC buildings designed according to Eurocode 8. Two families of RC buildings (i.e., 3 storey and 18 storey) are investigated using nonlinear static or push over analysis (POA). Each family of the buildings consists of five generic RC models with different behaviour factor namely 1, 1.5, 2, 4 and 6. The effect of behaviour factor to the buildings response characteristic parameters, i.e., elastic and inelastic stiffness, base shear strength at yield and maximum strength level and top displacement ductility are discussed thoroughly in this study. It is found that, the behaviour factor has a significant effect on the performance of RC buildings. Furthermore, this study also propose the relationship between displacement ductility and behaviour factor for high-rise and low-rise RC buildings and this equation which has high correlation factor can be used by designer or engineer to estimate the ductility capacity of low rise and high rise RC buildings based on their designed behaviour factor.